Have we been here before? Reviewing evidence of energy technology phase-out to inform home heating transitions. (July 2022) - Kerr, Niall; Winskel, Mark
Abstract: The rapid phase-out of fossil fuel home heating technologies is a formidable policy challenge. In such situations, referring to other cases of technology phase-out that are in some ways similar can offer useful insights, and a reassuring sense that 'we have been here before'. However, analogous reasoning of this kind tends to be partial and anecdotal, so it can mislead rather than inform. Here, we seek to draw more fully on analogous evidence to inform fossil fuel technology phase-out in the home heating sector, with particular reference to the UK. We review international energy technology phase-out experiences across three different sectors, five different technology types and twenty countries. We then assemble the evidence into an interpretive framework in which energy technology phase-out is seen as an outcome of distinctive but interacting techno-economic and socio-institutional factors and policy design issues, including: relative cost and performance, infrastructure and system context, public engagement and acceptability, incumbent interests and policy mixes and rationales. While some of these feature prominently in policy debates and transitions research, others command less attention. Providing a fuller representation of the factors involved in energy technology phase-out encourages more robust analogous reasoning in policy and research, recognising differences as well as similarities and the extent to which we have been here before. Highlights: Rapidly phasing-out fossil fuel home heating technologies is a formidable challenge. We review international evidence on energy technology phase-out experiences. We develop a novel framework of energy technology phase-out dynamics. Phase-out results from techno-economic, socio-institutional and policy design issues Important to recognise differences as well as similarities in analogous reasoning